2020
DOI: 10.21203/rs.3.rs-65379/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antimicrobial resistance in hospitalized surgical patients: a silently emerging public health concern in Benin

Abstract: Background: Surgical site infections are related to high morbidity, mortality and healthcare costs. Because the emergence of multidrug-resistant bacteria in hospitals is becoming a worldwide challenge for surgeons who treat healthcare-associated infections, we wished to identify the causative agents involved in these infections and the rate of multidrug-resistant bacteria in six public hospitals in Benin. Methods: Using standard microbiological procedures, we processed pus specimens collected from obstetrics … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This is consistent with a report in a previous study in Alexandria that in a sub-set of 65 isolates from SSI, half of the Gram-negative bacteria especially P. aeruginosa, Acinetobacter baumannii, and K. pneumoniae were resistant to carbapenem antibiotics [13]. The result from this study supports the trends reported on antibiotic resistance and indicates reduction efficacy of several classes of antibiotics including carbapenems, second and third generation cephalosporins, fluoroquinolones against gram negative bacilli, and extended-spectrum betalactamase inhibitor resistance amongst others [13].…”
Section: Antimicrobial Susceptibility Pattern Of Bacterial Isolatessupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with a report in a previous study in Alexandria that in a sub-set of 65 isolates from SSI, half of the Gram-negative bacteria especially P. aeruginosa, Acinetobacter baumannii, and K. pneumoniae were resistant to carbapenem antibiotics [13]. The result from this study supports the trends reported on antibiotic resistance and indicates reduction efficacy of several classes of antibiotics including carbapenems, second and third generation cephalosporins, fluoroquinolones against gram negative bacilli, and extended-spectrum betalactamase inhibitor resistance amongst others [13].…”
Section: Antimicrobial Susceptibility Pattern Of Bacterial Isolatessupporting
confidence: 93%
“…The threat posed by antibiotic resistance in the treatment of SSI remains a huge challenge to surgical patients as this contributes significantly to increased treatment cost, hospitalization time, as well as morbidity and mortality [13,14]. Many studies have reported that microbial virulence as well as host factor are very crucial determinants of surgical site infections [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Fofana et al [33] showed that AMR is the origin of important and continuous viral replication in children infected with HIV in Benin [34]. The question is more alarming when studies have shown multidrug-resistant strains involved in nosocomial infections in Benin [35,36]. A high rate of resistance to antibiotics commonly used for the treatment of infections has also been demonstrated [37].…”
Section: Status Of Amr In Beninmentioning
confidence: 99%